2008
DOI: 10.1080/10428230802070223
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oppressive Practice in Mental Health

Abstract: This article identifies the challenges to incorporating an anti-oppressive practice approach in the field of mental health, which has traditionally utilized a discourse and perspectives of a bio-medical model. Schools of Social Work often teach anti-oppressive and social justice approaches which make it difficult for students to link theory and practice in fields such as mental health. In this article, seven principles of practice are presented as a framework for working with people with disabling conditions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 13 publications
0
60
0
Order By: Relevance
“…Yet, given our experience in a school in which we often stand alone in our madness and have to correct our peers when they freely use the word crazy, she was not particularly surprised. Indeed, Larson's (2008) article is rare; silence continues to surround mental health in Canadian anti-oppressive spaces, and ignorance of how to change it and lack of interest in sensitizing each other to the effects of continuing on this path are problems.…”
Section: Moving Forward With Pedagogy and Research Around Madness Andmentioning
confidence: 95%
See 3 more Smart Citations
“…Yet, given our experience in a school in which we often stand alone in our madness and have to correct our peers when they freely use the word crazy, she was not particularly surprised. Indeed, Larson's (2008) article is rare; silence continues to surround mental health in Canadian anti-oppressive spaces, and ignorance of how to change it and lack of interest in sensitizing each other to the effects of continuing on this path are problems.…”
Section: Moving Forward With Pedagogy and Research Around Madness Andmentioning
confidence: 95%
“…Yet we had to start somewhere, taking the first steps toward more participation, more research, and more action, both internally and in the field. Taking up Larson's (2008) challenge, our first foray found that in our anti-oppressive school of social work, language and discourse are not always respectful, egalitarian and empowering when it comes to mental health. This includes, but is not limited to, the way madness is framed as a character deficiency as opposed to a group of people who, historically, have been marginalized.…”
Section: Moving Forward With Pedagogy and Research Around Madness Andmentioning
confidence: 98%
See 2 more Smart Citations
“…They further argue that a phenomenological reflexivity is essential not only for social work practitioners understanding these domains, but also for the wider -albeit controversial issue -of establishing a science of social work (p.512). I do acknowledge that reflexivity itself is not a panacea for either research or practice (Pillow, 2003), but it does encourage the practitioner to consider what hegemonic discourses are being produced and their impact on mental health practice (Larson, 2008;Morley, 2003).…”
Section: The Importance Of Reflexivity In the Practitionermentioning
confidence: 99%